DEVELOPMENT OF THE DOCTRINE OF FINANCIAL POLICY, THE FINANCIAL SYSTEM, FINANCIAL AND CREDIT MECHANISM AND FINANCIAL RESOURCES IN THE WORKS OF THE UKRAINIAN SCIENTIST MIKHAIL KRUPKA (World of finance, 2022)
Introduction. Each scientist contributes to the formation and development of financial theory and practice, which enriches financial science, makes it more powerful and effective. A special niche in this area is occupied by the Ukrainian scientist M. I. Krupka, who celebrates his 70th birthday in October 2021. His contribution to teaching in the areas of financial policy, financial system, financial and credit mechanism, financial resources is significant and occupies a worthy place in financial science, deserves study, generalization and dissemination. Therefore, the study of this problem is relevant.The purpose of the article is to study the current theoretical, methodological and practical foundations of financial policy, financial system, financial and credit mechanism, financial resources in the scientific works of the Ukrainian scientist M. I. Krupka and clarify recommendations for solving certain problems in this area in modern conditions.Methods. The work uses dialectical, structural-logical, institutional, functional approaches, methods of generalization, analysis and synthesis, induction and deduction, comparison, ascent from the concrete to the abstract and from the abstract to the concrete, assessment and others.Results. The main directions of scientific research of M. I. Krupka are revealed, in particular in the field of economic theory, money, credit and banking and finance. The approaches to the interpretation of financial policy, its influence on socioeconomic processes in society have been clarified. The definitions of the financial system, the features of its formation and functioning are considered. The nature, essence and main components of the financial and credit mechanism of the innovative development of the Ukrainian economy are analyzed. The theoretical, methodological and practical foundations for the formation and use of financial resources in Ukraine have been developed.